Genetic history from the Middle Neolithic to present on the Mediterranean island of Sardinia - Joseph H. Marcus (Nature Portfolio, 2020)
Ancient DNA analysis of early European farmers has found a high level of genetic affinity with present-day Sardinians. Here, the authors generate genome-wide capture data for 70 individuals from Sardinia spanning the Middle Neolithic to Medieval period to reveal relationships with mainland European populations shifting over time.